Determinants of Islamic Social Reporting (ISR) Disclosure On Financial Performance In Sharia Banking - Fitri Millenia, Hilwa; Hasan, Asyari (Green Publisher Indonesia, 2023)
This study aims to examine the effect of Islamic Social Reporting (ISR) disclosures on financial performance. The dependent variable used in this study is financial performance as measured by Return on Assets (ROA). The independent variable in this study is Islamic Social Reporting (ISR). The population in this study is the Islamic banking industry registered with the Financial Services Authority (OJK) for the 2011-2020 period. The sample in this study were 8 Islamic banks selected using purposive sampling method. This study uses panel data linear regression analysis as a data analysis tool. The statistical tool used was Eviews 9. The results showed that disclosure of Islamic social reporting had a significant positive effect on return on assets (ROA) with a prob value of 0.0102 or less than 0.05. So that ISR can be used to predict ROA with a positive coefficient direction, meaning that if ISR increases, ROA will increase, which means that financial performance will increase